Dynamiceuticals: The Next Stage in Personalized Medicine - Perez Velazquez, Jose L. (Frontiers in Neuroscience, 2017)
The surge in the interest in personalised medicine necessitates a corresponding rational approach for implementing such individualised therapies. Dynamiceuticals represents a natural extension of the Pharmacoceutical and Electroceutical fields, where the precise determination of the dynamical regimes of the pathophysiology will guide to devise therapies that ameliorate the pathology in a well-controlled manner, thus being precisely tailored towards the implementation of individualised medicine. This approach foretells to lessen side-effects and achieve superior efficacy as compared with current trial-and-error or open-loop strategies. But does the current state of knowledge and technology allow this scheme to offer what it claims?